Ixodes ricinus Salivary Serpin Iripin-8 Inhibits the Intrinsic Pathway of Coagulation and Complement - Kotál, Jan; Polderdijk, Stéphanie G I; Langhansová, Helena; Ederová, Monika; Martins, Larissa A; Beránková, Zuzana; Chlastáková, Adéla; Hajdušek, Ondřej; Kotsyfakis, Michail; Huntington, James A; Chmelař, Jindřich (International journal of molecular sciences, 2021)
Tick saliva is a rich source of antihemostatic, anti-inflammatory, and immunomodulatory molecules that actively help the tick to finish its blood meal. Moreover, these molecules facilitate the transmission of tick-borne pathogens. Here we present the functional and structural characterization of Iripin-8, a salivary serpin from the tick Ixodes ricinus, a European vector of tick-borne encephalitis and Lyme disease. Iripin-8 displayed blood-meal-induced mRNA expression that peaked in nymphs and the salivary glands of adult females. Iripin-8 inhibited multiple proteases involved in blood coagulation and blocked the intrinsic and common pathways of the coagulation cascade in vitro. Moreover, Iripin-8 inhibited erythrocyte lysis by complement, and Iripin-8 knockdown by RNA interference in tick nymphs delayed the feeding time. Finally, we resolved the crystal structure of Iripin-8 at 1.89 Å resolution to reveal an unusually long and rigid reactive center loop that is conserved in several tick species. The P1 Arg residue is held in place distant from the serpin body by a conserved poly-Pro element on the P' side. Several PEG molecules bind to Iripin-8, including one in a deep cavity, perhaps indicating the presence of a small-molecule binding site. This is the first crystal structure of a tick serpin in the native state, and Iripin-8 is a tick serpin with a conserved reactive center loop that possesses antihemostatic activity that may mediate interference with host innate immunity.
Keywords: lymeská nemoc; Animals; serpiny; Arthropod Proteins; Complement System Proteins; slinné žlázy; klíště; Serpins; Complement Activation; Salivary Glands; sliny; nymfa; erytrocyty; Blood Coagulation; aktivace komplementu; Nymph; regulace genové exprese; Saliva; Erythrocytes; Lyme Disease; exprese genu; Gene Expression Regulation; zvířata; proteiny členovců; hemokoagulace; komplement; Gene Expression; Ixodes